Effects of Multimedia-Assisted Learning on Learning Behaviors and Student Knowledge in Physical Education Lessons: Using Basketball Game Recording as an Example - Kao, Chun-Chieh; Luo, Yu-Jy (International Journal of Emerging Technologies in Learning (iJET), 2020)
The purpose of this study was to create a multimedia learning environment for use in PE lessons and to determine the effects of a traditional learning environment versus a multimedia learning environment on students’ learning behaviors and knowledge. This study had a pretest–posttest quasiexperimental design. The control and experimental groups comprised students at a Taiwanese university who were taught using the traditional teaching method (TT group; 48 students) and TMA (TMA group; 47 students). The pretest and posttest comprised the Learning Behavior Scale in Physical Education and a test questionnaire that assessed the students’ knowledge of basketball game recording methods through 32 multiple-choice questions. The teaching procedure lasted 4 weeks and covered various aspects of the rules of basketball, including the methods of recording basketball game scores. Differences between the groups were determined using various statistical tests. The students’ learning behaviors and knowledge of basketball recording methods were discovered to be significantly improved in both groups at the posttest. However, the TMA group outperformed the TT group, enhancing the students’ learning behaviors and knowledge to a greater degree. Overall, a combination of TT and TMA may have the most beneficial effect on students’ cognition and learning. Teachers should take their students’ current cognitive development into consideration when designing course materials.